Penetrating remote sensing solutions for Malaysia SDG urban monitoring system - Hj. Mohd. Noor, Norzailawati (2019)
. Globally space technologies are updating every day, the usage of it have been explored with new applications has been established particularly to accommodate sustainable development goals (SDGs) mission nowadays. The more open data platforms and tools available the more remote sensing data become widely accessible and usable especially for the countries that developing the possession of tasking rights to satellites and the needed processing capacity. The purpose of this study is assess the potential of open source and global datasets in estimating achievement of sustainable development goals (SDGs) number 11 particularly for urban area. Effort of using satellite imageries in related cases on urban monitoring has been analyzed. The result shows that the remote sensing dataset represent a high potential to supplement statistic for Malaysia achievement. We found that Malaysia government is committed in addressing the sustainable issues for the betterment of society, economy and environment for present and future undertakings with remote sensing solutions. However, the tune of country vision and mission recently influences a decision of this space data usage. The financial constraint, management and experts in accommodating space technologies making this solution in slow progressing. Hence, it will be a challenged for this country in surviving their urban monitoring system as well as SDGs mission for the future.